2022
DOI: 10.3324/haematol.2022.281339
|View full text |Cite
|
Sign up to set email alerts
|

All-trans retinoic acid works synergistically with the γ-secretase inhibitor crenigacestat to augment BCMA on multiple myeloma and the efficacy of BCMA-CAR T cells

Abstract: B-cell maturation antigen (BCMA) is the lead antigen for CAR T-cell therapy in multiple myeloma (MM). A challenge is inter- and intra-patient heterogeneity in BCMA expression on MM cells and BCMA downmodulation under therapeutic pressure. Accordingly, there is a desire to augment and sustain BCMA expression on MM cells in patients that receive BCMA-CAR T-cell therapy. We used all-trans retinoic acid (ATRA) to augment BCMA expression on MM cells and to increase the efficacy of BCMA-CAR T-cells in pre-clinical m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…Besides targeting distinct antigens, increasing target antigen density on MM cells also appears to be an appealing strategy. Several studies have proved that γ-secretase inhibitors and all-trans retinoic acid (ATRA) could upregulate BCMA expression on MM cells and facilitate their recognition by anti-BCMA CAR-T cells ( 40 , 41 ). In addition, ATRA could promote CD38 expression on MM cells ( 42 ).…”
Section: Resistance To Anti-bcma Car-t Cell Therapy In Multiple Myelo...mentioning
confidence: 99%
“…Besides targeting distinct antigens, increasing target antigen density on MM cells also appears to be an appealing strategy. Several studies have proved that γ-secretase inhibitors and all-trans retinoic acid (ATRA) could upregulate BCMA expression on MM cells and facilitate their recognition by anti-BCMA CAR-T cells ( 40 , 41 ). In addition, ATRA could promote CD38 expression on MM cells ( 42 ).…”
Section: Resistance To Anti-bcma Car-t Cell Therapy In Multiple Myelo...mentioning
confidence: 99%
“…However, responders had signi cantly higher baseline levels of surface BCMA expression compared to non-responders. In line with this observation, a recent preclinical study found out that increasing BCMA surface density by augmenting its expression with all-trans retinoic acid and preventing its shedding through gamma secretase inhibition improves e cacy of anti-BCMA CAR T cells 40 . Longitudinal single cell sequencing of peripheral blood allowed a detailed characterization of tiding malignant plasma cell clones and T cells.…”
Section: Discussionmentioning
confidence: 73%
“…The heterogenous expression of B-cell maturation antigen (BCMA), which is the primary CAR target in multiple myeloma, and BCMA shutdown under CAR-T-cell pressure pose crucial issues in the CAR-T-cell therapy of multiple myeloma [22,23]. Using the epigenetic modulator all-trans retinoic acid (ATRA) (Figure 1), BCMA expression could be augmented in multiple myeloma cell lines and primary multiple myeloma cells [24]. Additionally, the pharmacological upregulation of BCMA in myeloma cells eventuated in enhanced reactivity of BCMA-CAR-T cells in vitro and in vivo [24].…”
Section: Upregulation Of Target Antigensmentioning
confidence: 99%
“…Using the epigenetic modulator all-trans retinoic acid (ATRA) (Figure 1), BCMA expression could be augmented in multiple myeloma cell lines and primary multiple myeloma cells [24]. Additionally, the pharmacological upregulation of BCMA in myeloma cells eventuated in enhanced reactivity of BCMA-CAR-T cells in vitro and in vivo [24]. A combined treatment of myeloma cells with ATRA and the γ-secretase inhibitor crenigacestat (Figure 1) could further increase BCMA expression, inducing even stronger antigen-specific targeting by BCMA-specific CAR-T cells [24].…”
Section: Upregulation Of Target Antigensmentioning
confidence: 99%